Accuracy of Transcutaneous Carbon Dioxide Measurement in Premature Infants - Marie Janaillac; Sonia Labarinas; Riccardo E. Pfister; Oliver Karam (Critical Care Research and Practice)
Background. In premature infants, maintaining blood partial pressure of carbon dioxide (pCO2) value within a narrow range is important to avoid cerebral lesions. The aim of this study was to assess the accuracy of a noninvasive transcutaneous method (TcpCO2), compared to blood partial pressure of carbon dioxide (pCO2). Methods. Retrospective observational study in a tertiary neonatal intensive care unit. We analyzed the correlation between blood pCO2 and transcutaneous values and the accuracy between the trends of blood pCO2 and TcpCO2 in all consecutive premature infants born at <33 weeks’ gestational age. Results. 248 infants were included (median gestational age: 29 + 5 weeks and median birth weight: 1250 g), providing 1365 pairs of TcpCO2 and blood pCO2 values. Pearson’s R correlation between these values was 0.58. The mean bias was −0.93 kPa with a 95% confidence limit of agreement of −4.05 to +2.16 kPa. Correlation between the trends of TcpCO2 and blood pCO2 values was good in only 39.6%. Conclusions. In premature infants, TcpCO2 was poorly correlated to blood pCO2, with a wide limit of agreement. Furthermore, concordance between trends was equally low. We warn about clinical decision-making on TcpCO2 alone when used as continuous monitoring.